Pengaruh Karakteristik Wirausaha Dan Pemilihan Lokasi Usaha Terhadap Keberhasilan Usaha Dikampung Macuan Distrik Masni Kabupaten Manokwari - Desy Intan Pematasari Suriana; Makarius Bajari; Louis S. Bopeng (JFRES Journal of Fiscal and Regional Economy Studies, 2021)
Entrepreneurial characteristics and business location selection are factors that encourage the achievement of business success. This study aims to analyze the effect of entrepreneurial characteristics and business location selection on the success of a basic food stall business in Macuan Village, Masni District, Manokwari Regency. This type of research approach uses a quantitative approach. The population used in the study were all food stall entrepreneurs with a total of 46 respondents. The sampling technique used a saturated sample. The data used in this study are primary data and secondary data. The data collection technique used a questionnaire, while the data analysis used multiple linear regression analysis. The results show that partially entrepreneurial characteristics have a significant effect on business success, business location selection has a significant effect on business success, and simultaneously entrepreneurial characteristics and business location selection have a significant effect on business success. Some things that need to be considered by entrepreneurs include being confident, willing to take risks, future-oriented, strategic business locations, and frequent public transportation.